REPRESENTATION OF NEW MASCULINITY IN KEANU VERSION OF MS GLOW ADVERTISEMENT ON YOUTUBE: REPRESENTATION OF NEW MASCULINITY IN KEANU VERSION OF MS GLOW ADVERTISEMENT ON YOUTUBE - Achmad Wildan hermawan; Ririn Puspita T; Herlina Suksmawati; Yuli Candrasari (Universitas Islam Balitar, 2023)
Masculinity is a gender representation that is often used in advertising to persuade consumers. The purpose of this research is to reveal a new representation of masculinity in Keanu's version of Ms Glow advertisement on Youtube. This research focuses on the new masculinity depicted in Keanu's version of Ms Glow ad on Youtube. The data in this study are words, phrases, images, and colors that are in each scene of Keanu's version of Ms Glow's advertisement on Youtube. This study is included in qualitative research. The approach used in this research is John Fsike's semiotics which involves codes and signs. These signs and codes are a form of social practice. The new masculinity construction that appears is analyzed by paying attention to all aspects that exist in each advertising scene. The analysis carried out in this study was carried out in 3 stages, namely by paying attention to the level of reality, the level of representation, and the level of ideology. The results of this study indicate that the Keanu version of Ms Glow's advertisement on Youtube uses a new masculinity with the masculinity style found in this study, which is shown by showing a man who looks casual, has bright skin, and gestures that are graceful or waving. This shows the nature that leads to a new masculinity. The term new masculinity refers to a modern representation of masculinity. This modern masculine is not seen in the physical appearance that leads to social and culture.